Few-Photon Spectral Confocal Microscopy for Cell Imaging Using Superconducting Transition Edge Sensor - Niwa, Kazuki; Hattori, Kaori; Fukuda, Daiji (Frontiers in Bioengineering and Biotechnology, 2021)
A superconducting transition edge sensor (TES) is an energy-dispersive single-photon detector that distinguishes the wavelength of each incident photon from visible to near-infrared (NIR) without using spectral dispersive elements. Here, we introduce an application of the TES technique for confocal laser scanning microscopy (CLSM) as proof of our concept of ultra-sensitive and wide-band wavelength range color imaging for biological samples. As a reference sample for wide-band observation, a fixed fluorescence-labeled cell sample stained with three different color dyes was observed using our TES-based CLSM method. The three different dyes were simultaneously excited by irradiating 405 nm and 488 nm lasers, which were coupled using an optical fiber combiner. Even when irradiated at low powers of 80 nW and 120 nW for the 405 nm and 488 nm lasers respectively, emission signals were spectrally detected by the TES and categorized into four wavelength bands: up to 500 nm (blue), 500–600 nm (green), 600–800 nm (red), and 800–1200 nm (NIR). Using a single scan, an RGB color image and an NIR image of the fluorescent cell sample were successfully captured with tens of photon signals in a 40 ms exposure time for each pixel. This result demonstrates that TES is a useful wide-band spectral photon detector in the field of life sciences.